TORCH Infection during Pregnancy: A Comprehensive Review from Diagnosis to Treatment - Alrikaby, Nuha; Hami, Hasan; AL-Gorani, Amal; Vadayekheiry, Elahe (University of Thi-Qar Journal of Science, 2025)
TORCH is a group of pathogens that can infect a pregnant woman and subsequently transmit the infection to the fetus. These include the parasite Toxoplasma gondii, and other pathogens such as Treponema pallidum, parvovirus B19, rubella, Human cytomegalovirus, and herpes simplex virus. TORCH infections are among the most significant risks to fetal development, leading to congenital malformations and other complications transmitted from the mother and causes congenital malformations. Therefore, this review aims to provide a comprehensive overview of TORCH infection, including diagnostic methods, such as serological tests, PCR, and ultrasound imaging, to detect fetal malformations such as cerebral calcifications, hydrocephalus, and organ enlargement. The review also explained the treatment used for this infection, If a mixture of pyrimethamine and sulfadiazine is used with folic acid to treat, while the vaccine is used before pregnancy for the purpose of preventing German infection, as for CMV infection, acyclovir or ganciclovir is usually used, while penicillin is the treatment for Treponema pallidum. This review focuses on the clinical manifestations on the clinical manifestations of TORCH infection as a cause of congenital malformations in fetuses, presents the most important methods that can be used for accurate diagnosis, compares the protocols used for treating each infection in this group, and evaluates methods of prevention.